Sejam as matrizes :
O resultado de A + B é:
Soluções para a tarefa
Respondido por
0
A + B = X
Sabendo disso
A + B seria AB2
Ou
A2 + B2 = x2
(A.A). (B.B)=x2
AB. AB=x2
AB2 = x2
AB=X
Sabendo disso
A + B seria AB2
Ou
A2 + B2 = x2
(A.A). (B.B)=x2
AB. AB=x2
AB2 = x2
AB=X
ryan454825:
DNDD
Respondido por
0
Resposta:
A + B = X
Sabendo disso
A + B seria AB2
Ou
A2 + B2 = x2
(A.A). (B.B)=x2
AB. AB=x2
AB2 = x2
AB=X
Explicação:
Perguntas interessantes
Português,
7 meses atrás
Matemática,
7 meses atrás
ENEM,
7 meses atrás
Contabilidade,
7 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás